Neuroscience, Empathy, and Violent Crime in an Incarcerated Population: A Narrative Review - Saladino, Valeria; Lin, Hannah; Zamparelli, Elisa; Verrastro, Valeria (Frontiers in Psychology, 2021)
Empathy is a fundamental construct that allows individuals to perceive and understand the cognitive and emotional state of others. Empathy is not only a psychological and sociological concept; it also heavily impacts our daily lives by affecting our decisions and actions. Empathy is connected to and involves specific parts of the brain which, if damaged or of reduced volume, can lead to actions that are morally unjust, aggressive, or simply denoting a lack of understanding and sensitivity. The literature affirms that the low level of empathy, guilt, embarrassment, and moral reasoning displayed by violent and psychopathic criminals is strongly associated with empathy-linked brain regions that are smaller in size or less developed. The aim of this review is to show empirical data over the last 5 years on the connection between empathy and neuroscience among violent and psychopathic offenders, reflecting on future research on the topic.